'Who would even want to talk about death?' A qualitative study on nursing students' experiences of talking about death with terminally ill patients with cancer. (7th October 2021) - Üzar‐Özçetin, Yeter Sinem; Hiçdurmaz, Duygu; Öcalan, Sinem
Abstract: Objectives: This study aimed to describe nursing students' experiences of talking about death with terminally ill patients with cancer. Methods: The study adopted a qualitative design, and participants ( n  = 28) were final‐year undergraduate nursing students. Data were collected by conducting in‐depth semi‐structured face‐to‐face interviews using a pilot‐tested interview guide. The researchers followed a systematic data analysis procedure which is an appropriate method of analysis when aiming to create knowledge based on experiences and meanings from cross‐case analysis. Results: The responses of the nursing students were subsumed under the following three themes: (1) 'balance on the rope', (2) 'who would even want to talk about death' and (3) 'need to talk but …'. The findings suggest that many nursing students do not believe that they are competent enough to talk about death with terminally ill patients with cancer, even though they believe it is essential to end‐of‐life care. Conclusion: The findings underscore the importance of examining students' perspectives on death, which not only shapes their experiences of caring for terminally ill patients but also influences the quality of care. Further, students feel unprepared for talking to terminally ill patients with cancer and require support to avoid ignoring calls to speak about death.